PENGENDALIAN KUALITAS PRODUK MENGGUNAKAN PENDEKATAN SIX SIGMA DAN KAIZEN SEBAGAI USAHA PENGURANGAN KECACATAN PRODUK - Dhani Azis; Resista Vikaliana (Prodi Teknik Industri, Fakultas Teknik, 2023)
This study aims to provide a proposal on how to improve product quality and reduce the production of 1 liter long jerry cans of natural and matte colors using the help of PT Maju Kaya Rejeki Six Sigma DMAIC and Kaizen . Where problems regarding the final product are still common, even the final product is considered to be quite a lot. Data collection in this research is done by direct observation by looking at the production process and final product results and conducting interviews with related departments. After the data is obtained and processed, it is found that product factors still occur frequently and are caused by humans, machines, methods, materials, and the environment. Therefore, what is offered to reduce this is to strengthen relations with employees, create new work procedures, make employees to work under pressure, always carry out maintenance and inspection of machines, check and maintain raw materials, make adjustments to machines or production equipment, separate and grouping similar raw materials, arranging the layout of raw materials